Improvement of growth media quality using coconut coir dust, coconut ash, and palm kernel shell biochar - Amran, Natrah Azira; Kasim, Susilawati; Shuib, Effyanti Mohd; Yusoff, Martini Mohammad (Universitas Sebelas Maret, Indonesia, 2024)
The sustainable management of agricultural waste is vital for addressing environmental challenges while enhancing resource efficiency in agriculture. This study aimed to evaluate the potential of agricultural residues, specifically coconut and oil palm by-products, as growth media components. Growth media mixtures were formulated using coconut coir dust (CCD), coconut shell ash (CSA), and palm kernel shell biochar (PKSB), and their physicochemical properties were analyzed. The experiment was conducted in a completely randomized design with three replications. The results indicated that a growth media mixture consisting of 100% CSA demonstrated high pH (7.89), electrical conductivity (2.70 dS m-1), cation exchange capacity (12.57 cmolc kg-1), and significant concentrations of P (13.90 mg l-1) and K (191.70 mg l-1), which suggests its suitability as a liming agent. However, this mixture exhibited limitations in aeration and water retention due to low porosity (24.3%). Furthermore, increasing the proportions of CSA and PKSB significantly enhanced the growth media’s bulk density and particle density. These findings provide valuable insights into developing efficient growth media from agricultural by-products, thereby contributing to sustainable waste management and innovative farming practices.